The impact of 13-valent pneumococcal conjugate vaccination on virus-associated community-acquired pneumonia in elderly: Exploratory analysis of the CAPiTA trial. (July 2018) - Huijts, S.M.; Coenjaerts, F.E.J.; Bolkenbaas, M.; van Werkhoven, C.H.; Grobbee, D.E.; Bonten, M.J.M.; ,
Abstract: Objectives: Our objective was to evaluate whether vaccination with the 13-valent pneumococcal conjugate vaccine (PCV13) prevents the incidence of community-acquired pneumonia (CAP) caused by influenza (influenza-associated CAP, IA-CAP) or other respiratory viruses in the elderly. Methods: This analysis was part of the Community-Acquired Pneumonia immunization Trial in Adults (CAPiTA); a double blind, randomized, placebo-controlled trial in 84 496 immunocompetent individuals aged ≥65 years. CAP was defined by clinical and radiological criteria, and oropharyngeal swabs were collected from all individuals referred to a sentinel centre with a clinical suspicion of pneumonia. Presence of influenza A and B, parainfluenza 1, 2, 3 and 4, human adeno-, boca-, corona-, metapneumo-, rhino- and respiratory syncytial viruses was determined by real-time PCR. Results: Of 3209 episodes of suspected pneumonia, viral aetiology was tested in 2917 and proportions with influenza virus, human metapneumovirus and respiratory syncytial virus were 4.6%, 2.5% and 3.1%, respectively. There were 1653 oropharyngeal swabs for PCR testing available from 1814 episodes that fulfilled criteria for CAP, yielding 23 first episodes of IA-CAP in the PCV13 and 35 in the in placebo group—vaccine efficacy for IA-CAP of 34.4% (95% CI –11.1% to 61.2%; p 0.117). Annual influenza vaccination was received by 672 (87.2%) in the PCV13 group and 719 (87.7%) in the placebo group of the confirmed CAP cases. Conclusion: In a randomized study of 84 496 elderly individuals with a high uptake of influenza vaccination, PCV13 was not associated with a statistically significant reduction of influenza or virus-associated CAP. Overall incidence of non-influenza viral pneumonia was low.